A study on Pharm D Students Present Views and Future Plans (World Journal of Current Medical and Pharmaceutical Research, 2020)
Objective- This study aims to evaluate reasons for joining the Pharm D program among the graduates and students, their levels of satisfaction regarding choice, their perception towards the program and future career plans.Methods- All students and graduates under the Kerala University of Health Sciences, KUHS were invited to participate in the study conducted using the online portal- Google forms.Results- A total of 199 participants responded to the questionnaire, where the main reasons for choosing the program were to serve the society (88.4%), he/she is good at science (81.4%) and to settle and work abroad (70.9%). Working as hospital Clinical Pharmacist (87.9%) and Pharmacovigilance(80.4%) were the most preferred future career plans. About 59.8% respondents were ambitious towards pharmacy field.Conclusion- More than half of the respondents were satisfied to choose pharmacy and their reason for choice was to serve the society which outstood other factors and were more inclined to depict their skills in the field of pharmacovigilance and as clinical pharmacists.